PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPS MAN 4 TANAH DATAR - Melisa Tri Amiza (Jurnal Edukasi dan Penelitian Matematika, 2022)
Main point for achieving learning goals and other mathematical abilities is the mathematical understand concepts ability. However, in reality the mathematical understand concepts ability owned by students of class XI IPS MAN 4 Tanah Datar is low. The effort that can be made to improve that ability of student are to apply student teams achievement division (STAD) learning model. The goals of research is for to know and analysis whether mathematical understand concept ability of students uses the STAD model is better from mathematical understand concept ability of students uses the direct learning model and to know and describe the development of the mathematical understand concepts ability of students use the STAD learning model in students of class XI IPS MAN 4 Tanah Datar. The type of the research is quasi-experimental and descriptive research with non-equivalent posttest-only control group design. Result showed that mathematical understand concept ability of students uses the STAD learning model is better from mathematical understand concept ability of students uses the direct learning model. Then, the mathematical understand concept ability of students uses STAD cooperative learning model has increased significantly. Keywords – mathematical concept, STAD learning model, direct learning